Psychometric properties of the Spanish version of the climate anxiety scale in Spanish-speaking adolescents - Jimenez-Vazquez, David; Piqueras, Jose-Antonio; Espinosa-Fernandez, Lourdes; Canals-Sans, Josefa; Garcia-Lopez, Luis-Joaquin (Frontiers in Psychology, 2025)
IntroductionEvidence suggests that climate change affects both the physical and mental health of the global population. In this context, interest in research and in the development of reliable and valid tools to measure climate anxiety—defined as the experience of intense anxiety associated with perceptions of climate change—has increased.MethodsThe sample consisted of 1,065 respondents (49% self-identified as females) aged between 12 and 18 years (M = 14.0, SD = 1.49). This study is the first to evaluate the psychometric properties of the Climate Anxiety Scale, a 13-item questionnaire designed to assess anxiety as a psychological response to climate change, in a large population of Spanish-speaking adolescents.ResultsThe results showed a satisfactory model fit for the scale, with two subscales (cognitive-emotional impairment and functional impairment), both demonstrating adequate internal consistency. The subscales were invariant across gender, age, and socioeconomic status. Both subscales showed weak positive correlations with measures of emotional symptoms, emotional dysregulation, quality of life, and resilience—particularly for the functional impairment subscale. Network analyses indicated low centrality and connectivity of the CAS total score and subscales within the system. Overall levels of climate anxiety were low, though higher levels were observed among female adolescents, younger adolescents, and those from families with lower socioeconomic status.DiscussionThis study provides support for the use of the CAS in the Spanish-speaking adolescent population. The findings suggest that adolescent climate anxiety functions independently and reflects a complex emotional and existential response to the ecological crisis.